Role of luteinizing hormone elevation in outcomes of ovulation induction with letrozole for polycystic ovary syndrome - Fu, Wenyan; Kuang, Yanping (Frontiers in Medicine, 2023)
Introduction The effect of elevated luteinizing hormone (LH) on the clinical outcomes of ovulation induction (OI) in infertile anovulatory patients with polycystic ovary syndrome (PCOS) remains controversial. This retrospective study included PCOS patients undergoing intrauterine insemination (IUI) following letrozole (LE) stimulation without OC pretreatment. Materials and methods A retrospective cohort analysis was conducted in a single, academic ART center from January 2013 to May 2019. In total, 835 IUI cycles of PCOS patients treated with letrozole were collected for the analysis. Cohorts were separated based on the level of basal LH (bLH) and LH level after letrozole administration (LHle) during OI. OI response and reproductive outcomes were evaluated for each cohort. Results No adverse effects of dysregulated levels of either bLH or LHle on ovulation rate or reproductive outcomes were observed. Furthermore, the cohort of individuals with normal bLH and high LHle levels, exclusive of LH surge, exhibited significantly higher rates of clinical pregnancy (30.3% vs. 17.3%, p = 0.002) and live birth (24.2% vs. 15.2%, p = 0.024) than those with normal bLH and normal LHle. Conclusion These results indicated that high LH levels in PCOS are not solid evidence of poor prognosis of letrozole-induced ovulation, while elevated LHle may be a prospective predictor for better OI outcomes. It seems that preinhibition of LH secretion is not needed.